2000
DOI: 10.1038/sj.bjp.0703701
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and autonomic effects of ω‐conotoxins MVIIA and CVID in conscious rabbits and isolated tissue assays

Abstract: 1 The eects of a novel N-type voltage-operated calcium channel antagonist, o-conotoxin CVID, were compared with o-conotoxin MVIIA on sympathetic-evoked activation of right atria (RA), small mesenteric arteries (MA) and vasa deferentia (VD) isolated from the rat. Their eects were also compared on blood pressure and cardiovascular re¯exes in conscious rabbits. 2 The pIC 50 values for MVIIA and CVID, respectively, for inhibiting sympathetic-evoked responses were equivalent in RA (8.7 and 8.7) and VD (9.0 and 8.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 32 publications
(46 reference statements)
3
51
0
Order By: Relevance
“…When a relatively low CTx dose (10 μg/kg) was intravenously administered into rats, in fact, we could not observe any apparent difference between CTx-FVIA and CTx-MVIIA in recovery pattern of blood pressure. Similarly it was reported that Wright et al used a high dose of toxin (100 μg/kg) in an experiment for cardiovascular and autonomic effects [60]. As with its effect on N-type Ca 2+ currents, the effect of CTx-FVIA on blood pressure was more reversible than that of CTx-MVIIA (Figure 2C and Figure 6).…”
Section: Discussionsupporting
confidence: 69%
“…When a relatively low CTx dose (10 μg/kg) was intravenously administered into rats, in fact, we could not observe any apparent difference between CTx-FVIA and CTx-MVIIA in recovery pattern of blood pressure. Similarly it was reported that Wright et al used a high dose of toxin (100 μg/kg) in an experiment for cardiovascular and autonomic effects [60]. As with its effect on N-type Ca 2+ currents, the effect of CTx-FVIA on blood pressure was more reversible than that of CTx-MVIIA (Figure 2C and Figure 6).…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, the block by -conotoxin CVIB, an antagonist of both N-and P/Q-type VGCCs, has been shown recently to reversibly inhibit excitatory synaptic transmission in the spinal cord (Motin and Adams, 2008). Recovery from block may influence how effectively -conotoxins reverse different painful conditions in vivo, and could indicate whether administration of these peptides can be controlled to avoid unwanted side effects (Wright et al, 2000).…”
mentioning
confidence: 99%
“…A transverse section of tissue 1 to 2 mm thick was cut from the construct, placed immediately in physiological salt solution 26 at 37°C, and saturated with 95% O 2 and 5% CO 2 during the experiment. The tissue was mounted vertically between stainless steel S-shaped hooks on an acrylic leg in physiological salt solution-filled 20-mL glass-jacketed organ bath heated to 37°C.…”
Section: In Vitro Organ Bath Studymentioning
confidence: 99%